Determinants of Islamic Banking Customer Decisions: Social Environment, Financial Literacy, and Brand Image - Dewi Maharany, Indah; Lestari, Dewi; Hanggono Raras, Mardawaning; Habibah, Muzayyidatul (Universitas Islam Nahdlatul Ulama Jepara, 2024)
The micro, small, and medium enterprise (MSME) sector is experiencing tremendous growth and has made significant contributions to overall economic expansion. When managing their funds, MSMEs should take into account the different storage and investment choices at their disposal, including the emerging field of sharia banking, which offers goods and services that adhere to sharia principles. This study seeks to identify the elements that influence the decision of MSME actors to become customers in sharia banking. The independent variables considered are social environmental variables, financial literacy, and brand image, while the dependent variable is the decision of MSME actors. This study employs primary data collection methods and adopts a quantitative research strategy. The research employed a purposive sampling strategy to select a sample size of 100 respondents. The data was analyzed using multiple linear regression analysis, coefficient of determination, F test, and t test in SPSS. The research findings indicate that the social environment, financial literacy, and brand image all have a substantial impact on the decision of MSMEs to become customers in sharia banking